2007
DOI: 10.1016/j.vetpar.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Ostertagia ostertagi with subfractions of the protective ES-thiol fraction

Abstract: Previous vaccination trials against Ostertagia ostertagi in cattle have demonstrated the protective capacity of a protein fraction termed ES-thiol, which is enriched for activation-associated secreted proteins (ASPs) and cysteine proteases. In this study, ES-thiol was subfractionated through Q-Sepharose anion exchange chromatography to determine whether the ASPs and/or the cysteine proteases are responsible for the induced protection. Calves (seven/group) were immunized three times intramuscularly with 100 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 23 publications
(40 reference statements)
6
48
0
Order By: Relevance
“…1A. The group of animals vaccinated with the ASP-based vaccine in combination with QuilA as an adjuvant showed a significant (P Ͻ 0.05) reduction in the cumulative fecal egg count (cumEPG) of 59%, which is consistent with previous trials in which a similar reduction in the cumulative number of EPG of feces was observed (14,16). Although it was not significant, there was also a small reduction in the total number of worms counted (20%) and in the average length of female worms (3%).…”
Section: Vaccination Trialsupporting
confidence: 87%
See 3 more Smart Citations
“…1A. The group of animals vaccinated with the ASP-based vaccine in combination with QuilA as an adjuvant showed a significant (P Ͻ 0.05) reduction in the cumulative fecal egg count (cumEPG) of 59%, which is consistent with previous trials in which a similar reduction in the cumulative number of EPG of feces was observed (14,16). Although it was not significant, there was also a small reduction in the total number of worms counted (20%) and in the average length of female worms (3%).…”
Section: Vaccination Trialsupporting
confidence: 87%
“…Helminth-naïve calves were infected with 200,000 O. ostertagi infective larvae (L3) and euthanized 3 weeks later to collect adult worms from the abomasum. O. ostertagi adults were cultured, and ES proteins were collected from the culture supernatant as previously described (16). The ASP subfraction was purified from total adult ES by thiol Sepharose chromatography, followed by anion-exchange chromatography as previously described (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are of general interest as they have shown their protective capacity in multiple vaccination trials against Ancylostoma spp., H. contortus and O. ostertagi (Schallig et al, 1997a;Ghosh and Hotez, 1999;Geldhof et al, 2002Geldhof et al, , 2004Goud et al, 2004;Meyvis et al, 2007). Three types of ASP proteins have been identified in nematodes: long ASP proteins composed of two distinct but related domains and short ASP molecules that show similarity to either the C-terminal or the N-terminal domain of the double-domain ASP.…”
Section: Introductionmentioning
confidence: 99%